Social Justice from Hayek's Perspective - de Castro Neves, Ana Paula; Castro, Luciano Rodrigues; Sanz, Wagner de Campos (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article aims to present a study of Friedrich August von Hayek's critical approach, from the denomination to the application of Social Justice. To achieve this goal, we sought, through a descriptive theoretical research, to analyze the way in which Hayek's concepts are articulated through a detailed exposition of his works, above all, on the fundamentals of Social Justice.